Changes in maximal strength and body composition after different methods of developing muscle strength and supplementation with creatine, L-carnitine and HMB - Kruszewski, M. (Biology of Sport, 2011)
The aim of the present study was to assess the effects of bodybuilding training combined with administration of L-carnitine, weightlifting training combined with administration of creatine, and isometric training combined with administration of ?-hydroxy-?-methylbutyrate (HMB) on maximal strength and body composition of athletes. The studies were conducted on groups of beginners practising bodybuilding training (n=63) and isometric training (n=69) as well as on a group of advanced powerlifters (n=50) practising weightlifting training. The obtained results indicate that the most desirable and beneficial supportive effect in strength sports was exhibited by HMB. No significant differences in body composition of subjects practising bodybuilding training were detected between those who were given L-carnitine and those who received placebo, an observation confirming controversies over the capacity of the former to reduce fat content. However, significant differences in maximal strength were demonstrated between the examined groups of athletes. Significant differences in the examined parameters were also detected within the group of advanced powerlifters practising weightlifting between those who were supplemented with creatine and those who were given placebo. Thus, the use of creatine in the development of physical capacity in advanced athletes may be advisable.